Odpowiedzi

2009-12-13T18:24:42+01:00
(22/10-15/10)*9/10+1/4-1=
=126/20-15/20=111/20=5 11/20
2009-12-13T18:25:50+01:00
(₂⅕-₁⅓)×(₀.₉)+(⅓)²-(₁.₇)⁰ =(11/5-4/3)×9/10+1/9-1=
(33/15-20/15)×9/10+1/9-8/9=
13/15×9/10-8/9=13/5×3/10-8/9=39/50-8/9=351/450-400/450=-49/450

2009-12-13T18:25:07+01:00
(₂⅕-₁⅓)×(₀.₉)+(⅓)²-(₁.₇)⁰ =
(11/5 - 4/3)×(₀.₉) + 1/9 - 1=
11/5 mnożę przez 3
4/3 mnożę przez 5
= (33/15 - 20/15)×(₀.₉)+1/9 - 1=
= 13/15 × (₀.₉) + 1/9 - 1 =
= 0,78 + 1/9 - 1 =
= -0,22 + 1/9 =
= - 22/100 + 1/9 =
= - 11/50 + 1/9 =
-11/50 mnożę przez 9
1/9 mnożę przez 50
= - 99/450 + 50/450 =
= -49/450